Clinical utility of complement‐dependent C3d assay in kidney recipients presenting with late allograft dysfunction. Issue 12 (9th May 2018) - Lan, James H; Gjertson, David; Zheng, Ying; Clark, Stephanie; ,; Reed, Elaine F; Cecka, Michael J
Abstract: The objective of this study was to evaluate the utility of a complement‐dependent C3d assay to risk stratify donor‐specific antibodies (DSA) in a multicenter cohort of kidney recipients presenting with new‐onset clinical dysfunction. A total of 106 subjects with evidence of DSA at a mean period of 5.3 ± 5.0 years posttransplant underwent testing using C3d reagents. C3d positivity was strongly associated with both the peak and sum IgG DSA MFI, with 98.3% (n = 57/58) of strongly reactive sera (peak MFI > 10 000) eliciting a positive signal. Patients with C3d+ DSA had a higher creatinine ( P = .03), more significant graft fibrosis ( P = .035), and a faster rate of graft loss posttest compared to those with C3d‐ DSA ( P = .05). Subanalysis of patients with low‐moderate level DSA confirmed the inferior outcome associated with C3d positivity. Despite the prognostic value of C3d as a stand‐alone test, the assay did not provide independent risk prediction after incorporation of graft fibrosis in a multivariate model ( P = .94). Overall, C3d offered limited discriminatory value for strong DSA with peak IgG MFI > 10 000 and in patients where histologic data is available, but its utilization may be considered in those with low‐moderate level DSA and where an allograft biopsy is not accessible. Abstract : This study evaluates the prognostic value of a C3d assay in a cohort of kidney recipients, demonstrating that while C3d+ donor‐specific antibodies associate with inferior graft survival compared to C3d– antibodies, the assay provides marginal value in the risk stratification of patients with strong donor‐specific antibodies.